AI-infused web décor shop - Wee, Cindy Zi Wei (2023)
In an age where reliance on the internet is ubiquitous, the transformation of traditional retail stores into online counterparts has become a necessity. This paradigm shift addresses the needs and preferences of a digitally connected populace. To tackle this challenge, an AI-infused web decor shop is proposed, offering a seamless shopping experience for both customers and management teams. The core objective of this web application is to streamline administrative tasks while providing customers with convenient access to an array of products, eliminating the need for physical store visits. Targeted users encompass a wide spectrum, including customers seeking personalized decor solutions and the management team comprising administrators, staff, and shop owners. Harnessing the power of AI technology, this innovative platform empowers customers to customize and curate their ideal decor, enhancing the allure of their memorable occasions. By seamlessly integrating AI, customers are enabled to transform their visions into reality with ease. The development of this system adheres to a phased approach, aligning with the project's scope. Each phase focuses on essential modules crucial for the platform's functionality. Upon system completion, rigorous testing was conducted to ensure compliance with project requirements. User acceptance tests yielded overwhelmingly positive results, with most users rating their satisfaction levels at more than 4 out of 5. In conclusion, this research demonstrates the successful fulfillment of its objectives, offering a compelling solution to the imperative need for online retail transformation in the digital age.